Enteric fever in a young man with bowel wall thickening and hepatosplenomegaly - Suarez-Silva, David (2024)
Typhoid fever (enteric fever), caused by Salmonella enterica subsp. enterica serovar Typhi (S. Typhi), is a public health problem especially in South Asia and sub-Saharan African countries, while incidence remains low in most other parts of the world, where the disease is primary related to recent travel to endemic countries or contact with chronic carriers. The diagnosis of typhoid fever is challenging in endemic countries, often also low- and middle- income countries (LMIC), due to the poor sensitivity/specificity of available serologic tests and lack of adequate infrastructure for blood cultures. We report the case of an 18-year-old male patient with a 21-day history of right-sided abdominal pain, malaise, headache, intermittent fever and watery diarrhea. Contrast-enhanced abdominal computed tomography (CT) exhibits thickening of the terminal ileum, cecum and ascending colon with mesenteric lymphadenopathy. Laboratory findings indicate elevated transaminases, positive blood culture to S. Typhi and a positive Widal test to S. Paratyphi A, B and S. Typhi H (flagellar) antigens. A diagnosis of complicated typhoid fever was made. Following a 13-day regimen of ceftriaxone, all symptoms resolved. Few reports have been made about CT manifestations in patients with typhoid fever. While CT can aid in diagnosis, it is particularly important for identifying complications of typhoid fever such as perforation, bleeding and abscess formation.